Stabilization And Characterization Of Heavy Crude Oilin-Water (O/W) Emulsions - Liyana, M. S.; Nour, A. H.; Rizauddin, D.; Jolius, Gimbun (eSAT Publishing House Pvt. Ltd., 2014)
There has been much interest in alternative to transport viscous crude oil from reservoir which is much more abundant than conventional oil. There are many authors hard to find the stable of oil-in-water (o/w) emulsion condition which has been considered as critical analysis. In order to reduce the viscosity, the heavy oil is required to modify for reducing their viscosity. Applying diluent and forming o/w emulsion are the selected as alternative for reducing viscosity. The purpose for this investigation is to study factors that influencing stability and viscosity of o/w emulsion. From the observation, o/w emulsions reduced almost six (6) times less than original heavy oil. However, the addition of 40% of light oil reduced oil viscosity from 478.10 mPa.sto 113.40 mPa.s. Thus, the knowledge and understanding factors that influencing the stability and viscosity of o/w emulsion is important due to avoiding of occurring phase inversion phenomena.